Dutch-Flemish translation and validation of the gastrointestinal symptom scales from the patient‑reported outcomes measurement information system (PROMIS)® - Mirjam van der Ende-van Loon; Dorinde Korteling; Hilde Willekens; Monique Schilders; Wouter Curvers; Raf Bisschops; Erik Schoon; Caroline Terwee (SpringerOpen, 2023)
Abstract Purpose To translate the eight PROMIS® GastrointestinaI Symptom Scales into Dutch-Flemish and to evaluate their psychometric properties. Methods This study consisted of two parts: (1) translation according to the Functional Assessment of Chronic Illness Therapy (FACIT) translation methodology and (2) evaluation of psychometric properties: structural validity, using confirmatory factor analysis; and construct validity using hypothesis testing. Results In the first part of the study, in 19 out of the 77 items (24.7%) translation was challenging. After discussion between the translators, consensus could be achieved. In the cognitive debriefing interview phase, ten minor changes in the wording of items were made. A universal Dutch-Flemish translation for all 77 items was obtained. In de second part of the study a good fit was found for three DF-PROMIS GI Scales: Bowel Incontinence, Gas and Bloating, and Belly Pain. Four scales (Reflux, Disrupted Swallowing, Diarrhea, and Constipation) did not show sufficient fit and fit for the Nausea and Vomiting scale could not be assessed because of skewed responses. Construct validity was considered sufficient for six out of eight DF-PROMIS GI Scales. Less than 75% of hypothesis for de Constipation and Disrupted Swallowing scales could be confirmed. Conclusion The PROMIS GI Symptom Scales were successfully translated into DutchFlemish. The findings suggest a sufficient structural validity for the PROMIS GI Scales. Bowel Incontinence, Gas and Bloating and Belly Pain. Construct validity was sufficient for the Scales Gas and Bloating, Incontinence, Nausea and Vomiting, Reflux, Belly Pain, and Diarrhea.